A synchronized multi-staged thermal energy storage system for sustainable hydroponic greenhouses - Erdemir, Dogan; Dincer, Ibrahim; Bicer, Yusuf (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
This study develops and evaluates an innovative integrated solar-powered system which is integrated with a novel three-level synchronized latent heat storage system to provide a sustainable and continuous supply of electricity, freshwater, and heat for greenhouse applications, particularly focusing on arid regions like Doha, Qatar. This latent heat storage system offers better management and lower exergy destruction compared to the conventional heat storage systems. The system centers around parabolic trough solar collectors (PTCs). While power generation is achieved via an organic Rankine cycle (ORC) using toluene as the working fluid, freshwater is produced using a multi-stage flash (MSF) desalination unit. A key innovation is the incorporation of a cascaded thermal energy storage (TES) system with phase change materials. The present TES system features three modules operating at distinct temperature levels which are high: 200-225 degrees C for power generation, medium: 150-175 degrees C for desalination, and low: 80-90 degrees C for greenhouse thermal management, enabling synchronized energy storage and discharge to compensate for solar intermittency and meet varying demands. Thermodynamic performance is assessed using energy and exergy analyses. The results indicate that system outputs (electricity, heat, and freshwater) scale linearly with the PTC area, demonstrating predictable performance and modularity. As confirmed through a case study, a 10,000 m2 PTC area can yield approximately 77 m3 of freshwater daily. The overall system maintains stable energy (19.4 %) and exergy (12.5 %) efficiencies across tested scales, though the difference highlights potential for optimization by minimizing thermodynamic irreversibilities. The TES system presented in this study enhances exergy efficiencies by 3.62 %. The integrated TES is crucial for extending operational hours, ensuring consistent resource production beyond direct solar availability. This integrated approach offers a robust solution for enhancing resource and food security and sustainability in arid environments.
Keywords: Agriculture; Desalination; Efficiency; Exergy; Heat storage; Organic Rankine cycle; Phase change material; Solar energy; Thermodynamics; Energy & Fuels; Engineering; Mechanics